2018
DOI: 10.1186/s40798-018-0137-0
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Correlates and Determinants of Cardiorespiratory Fitness in the General Adult Population: a Systematic Review and Meta-Analysis

Abstract: BackgroundThis review aims to (1) consolidate evidence regarding the association between socioeconomic status (SES) and cardiorespiratory fitness (CRF), (2) conduct a meta-analysis of the association between SES and CRF using methodologically comparable data, stratified by sex, and (3) test whether the association varies after adjustment for physical activity (PA).MethodsA systematic review of studies from MEDLINE, EMBASE, Latin American and Caribbean Health Sciences (LILACS), Scientific Electronic Library Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 103 publications
4
20
0
2
Order By: Relevance
“…Age (continuous), education (four categories: compulsory, upper secondary, university, higher academic education), gender (man, woman), smoking (yes, sometimes, no), and general health (very good, good, fair, poor, very poor) were based on self-reported data from the baseline questionnaire. These covariates were included based on earlier research regarding their associations with the exposures and outcomes [9,[39][40][41][42][43][44][45].…”
Section: Methodsmentioning
confidence: 99%
“…Age (continuous), education (four categories: compulsory, upper secondary, university, higher academic education), gender (man, woman), smoking (yes, sometimes, no), and general health (very good, good, fair, poor, very poor) were based on self-reported data from the baseline questionnaire. These covariates were included based on earlier research regarding their associations with the exposures and outcomes [9,[39][40][41][42][43][44][45].…”
Section: Methodsmentioning
confidence: 99%
“…performed in order to identify potential individual and socioeconomic correlates of CRF 8,14,16 . Potential interpersonal correlates of CRF were derived from evidence regarding the association of these factors and PA 12,27,28 .…”
Section: Potential Correlates Of Cardiorespiratory Fitness a Comprehmentioning
confidence: 99%
“…3 Relatively lower levels of leisure time physical activity and CRF have been reported in low SES individuals as compared with those of high SES groups. 4 Previous studies have also reported that the low CRF levels in low SES individuals could in part explain the socioeconomic disparities in all-cause mortality. 5,6 Low leisure time physical activity may be fostered by lack of resources in socioeconomically deprived neighborhoods, such as the absence of sidewalks, fewer accessible recreational facilities, relatively unsafe outdoor exercise environments and reduced opportunities to engage in leisure time physical activity.…”
mentioning
confidence: 98%